Trade Policies and Lithuania's Reintegration Into the Global Economy - Cornelius, Peter (IMF Working Papers; Working Paper ;, 1995)
The reintegration into the world economy has been an integral part of Lithuania's transformation process. Trade policy reform has been assigned a key role, aiming at opening up the economy and redirecting foreign trade. This paper (i) analyzes the trade shock following the dissolution of the former Soviet Union; (ii) studies the political economy of trade reforms; (iii) evaluates Lithuania's attempts to gain greater access to Western markets, in particular the European Union; and (iv) reviews the empirical evidence on redirecting foreign trade.